Being a Black Mother Living with HIV Is a “Whole Story”: Implications for Intersectionality Approach - Etowa, Josephine B.; Kakuru, Doris M.; Etowa, Egbe B. (Women (Basel, Switzerland), 2022)
While African, Caribbean, and Black (ACB) mothers living with HIV in Canada are required to follow public health guidelines by exclusively formula feeding their infants, they also face cultural expectations from peers and family members to breastfeed. They face multiple challenges because of their race, ethnicity, gender, class, and geographical location, among other factors. Previously published studies on this subject did not analyze how the intersectionality of these factors impacts Black mothers’ infant feeding experiences. In this article, we discuss the infant feeding practices of Black mothers living with HIV in Ottawa (Canada). We followed a qualitative methods research design that utilized intersectionality and a community-based participatory research approach. We used the intersectionality framework as a lens to analyze the complex mesh of determinants influencing motherhood experiences of ACB women living with HIV. Being a Black/ACB mother while living with HIV is a “whole story” permeated with cutting-across issues such as race, class, gender, socio-political, and cultural contexts. These issues are interwoven and often difficult to unravel. Multiple layers of structural determinants of Black/ACB women’s HIV vulnerability and health are described. Intersectionality is important for an in-depth understanding of societal power dynamics and their impact on women’s health inequities.